Breaking Solvation Dominance Effect Enabled by Ion–Dipole Interaction Toward Long-Spanlife Silicon Oxide Anodes in Lithium-Ion Batteries - Shengwei Dong; Lingfeng Shi; Shenglu Geng; Yanbin Ning; Cong Kang; Yan Zhang; Ziwei Liu; Jiaming Zhu; Zhuomin Qiang; Lin Zhou; Geping Yin; Dalong Li; et al. (Nano-Micro Letters)
Highlights The succinonitrile-based deep eutectic electrolyte, characterized by strong ion–dipole interactions, can establish an anion-rich Li+ solvation structure while exhibiting high ionic conductivity and Li+ transference number. Precisely regulating multiple ion–ion, ion–dipole, and dipole–dipole interactions facilitates the transition of the Li+ solvation structure from solvent dominance to anion dominance. Optical microscopy and Micro-CT analysis can demonstrate that the anion-derived solid electrolyte interphase effectively mitigates the irreversible volume expansion of silicon oxide.